PENERAPAN METODE LEAN PROJECT MANAGEMENT DALAM PROYEK KONSTRUKSI PADA PEMBANGUNAN GEDUNG DPRD KABUPATEN OGAN ILIR - Dian Artika (Jurnal Teknik Sipil dan Lingkungan, 2014)
In a construction project required resources, cost, labor, materials, and equipment. A project said to be good if the completion of the project is efficient in terms of time, cost, and achieve work efficiency, people and tools. And vice versa if the project failed and the late completion of the project budget to swell. Delays on the project can be caused by unproductiveness elements involved in project implementation. Everything in a project that does not add value, otherwise add to the cost of so-called waste. To overcome these problems needed improvements in planning the approach of Lean Project Management ( LPM ). In this research, the identification of waste, risk, and estimates the needs of the project (time, resources, and costs), as well as the estimated time scheduling using Critical Chain Project Management ( CCPM ). Based on identification of research on building construction projects Ogan Ilir district legislature, obtained waste that could potentially arise during the implementation of the project is waiting. The presence of waste will result in project delays, for that we need the safety time (buffer time) contained in scheduling with CCPM method. CCPM scheduling method obtained from a total cost savings of Rp 1.616.664.000 of the reduction in the number of workers.Keywords : Waste , Lean Project Management , Critical Chain Project Management